Pengaruh Prinsip Non-Intervensi ASEAN terhadap Upaya Negosiasi Indonesia Dalam Menangani Konflik Kudeta Myanmar - Zahratunnisa Ramadhani; Mabrurah Mabrurah (Global Political Studies Journal, 2021)
On 1 February 2021 Myanmar's democratization was once again threatened, following a military junta coup against the Government of Myanmar, by detaining several leaders, including Myanmar President Win Myint and Aung san suu kyi, the State Advisor. This study aims to analyze the Indonesia government's efforts to disarm the current conflict in Myanmar, while still respecting the principle of non-intervention, a mutual agreement between the ASEAN members. The method of research chosen is qualitative descriptive using techniques used for data collection through journals, papers, web sites and other reliable sources. Moreover, to strengthen the argument, the author uses the constructivism theory of Alexander Went which is linked by an analysis of Indonesia's efforts in the conflict in Myanmar. This study focuses on the effect of the ASEAN non-intervention principle on Indonesia's conflict resolution efforts. The results of this study show that the application of the ASEAN principle of non-intervention by ASEAN on the one hand gives Member States the flexibility to solve their internal problems without any interference from other countries. however, on the other hand, this principle becomes a barrier for ASEAN member countries to implement certain mechanisms in some cases, such as the current case of the coup conflict. Keywords : The principle of non-intervention, Myanmar Conflict, Negotiation